融着帯圧力損失推定モデルによる通気性に及ぼすコークス層厚の影響の評価 - 柏原, 佑介; 石井, 純; 廣澤, 寿幸; 松野, 英寿; 市川, 和平; 大山, 伸幸; 佐藤, 道貴 (鉄と鋼, 2016)
Recently, the price of coke has increased, so low coke rate operation has been required in the blast furnace. On the other hand, coke layer thickness decreases in low coke rate operation. It is known that gas permeability of the blast furnace becomes worse in thin coke layer thickness. So it is important to know minimum coke layer thickness. But minimum coke layer thickness has not been clear. That’s because there were no equipment to measure the effect of coke layer thickness on permeability. In this study, to clarify the minimum coke layer thickness, new experiment equipment called cohesive zone simulator was developed. In a cohesive zone, gas flow along with coke layer, horizontally. To measure the effect of coke layer thickness on permeability, horizontal gas flow should be simulated. Therefore this simulator simulates horizontal gas flow. Next, the effect of coke layer thickness was quantified by using the cohesive zone simulator. By the results, melting ore was penetrating into coke layer and closed part of layer. These phenomena caused increasing permeability in thin coke layer thickness condition. Finally, pressure drop estimation model considering melting ore penetration was developed for the aim of quantifying minimum coke slit thickness.